Produção de proteases e celulases fúngicas a partir do engaço de uva - Andrade, Eline de Souza Pontes (2022)
The processing of grapes for wine production generates residues, such as: stalk, skin, seeds and pomace, which are usually discarded improperly. These residues can be used by wineries as organic fertilizer or destined for animal feed. However, in recent years, they have been considered a cheap and rich source of bioactives. Among these residues from grape processing, stalk can be considered an interesting raw material for industrial bioconversion processes, since it has a high content of lignin, cellulose and hemicellulose. Such a composition allows it to be used as a substrate in biotechnological processes, mainly in the production of microbial enzymes. Thus, this work sought to use grape stalks (Vitis labrusca) provided by Empresa Sabores de Frutas Santa Maria, located in the Chã do Esquecido district of the municipality of São Vicente Férrer - PE, in the solid state process by the action of Paecilomyces sp. TP08 and Aspergillus sp, NA01 for the production of cellulolytic and proteolytic enzymes. The stalk was prepared and characterized in terms of moisture (70%), pH (4), porosity (0.39g/cm3), reducing sugars (0.44g/L) and total reducing sugars (1.00g/L). For enzymatic production, erlenmeyer flasks (125mL) with 5g of grape stalks inoculated with a conidia suspension of 1x107 conidia per gram of solid substrate were used. Humidity was adjusted to 70% and room temperature to ±30ºC. After 10 days of process, the enzymatic complex was extracted from the cultivated substrate to determine the enzymatic activity. Cellulolytic activity obtained was 2.11U/g for FPase, 7.48U/g for CMCase and proteolytic activity of 26.39 U/g from the isolate Paecilomyces sp. TP08, and for the isolate Aspergillus sp. NA01 was 11.41U/g for CMCases, 1.73 U/g for FPases and 8.17 U/g for proteases. In view of the results, the potential of using grape stalks for the production of microbial enzymes, mainly cellulolytic and fungal proteolytic enzymes, was verified.